Analysis of CO2 emissions and economic impacts for Turkey using Times - Macro energy modeling system - Alizade, Shadi Firouzi. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
There has been growing consideration about the intensity of greenhouse gases in the atmosphere as a trigger of climate change. This issue has resulted in the need to deﬁne targets for abating carbon emissions. Turkey’s CO2 emissions have tripled in the period 1990-2012. It is therefore needed to examine Turkey’s energy sector to un derstand the leading cause of skyrocketing emissions and elaborate the policy options to reduce emissions. The costs associated with emission reductions are also inﬂuential on the national economy. In order to be able to analyze these interactions, this thesis deﬁnes a model to examine the economic impacts of emission constraints and presents a baseline for policy makers. The TIMES-MACRO modeling framework has been em ployed in this thesis which is a hybrid energy system and economic growth model. Using this modeling framework, Turkey’s energy sector and CO2 emissions have been evaluated together with the economic implications. Following an overall overview of the model, the behavior of the Turkey energy sector under a business-as-usual scenario, under carbon constraints and under carbon taxes have been comparatively evaluated. The main focus of this thesis is to assess the eﬀects of emission constraints on the energy sector, evaluate costs and the subsequent impacts on the entire economy. The model is calibrated under a reference scenario along with various policy scenarios con sidering the same resource availability, macroeconomic assumptions and technological characteristics, but applying diﬀerent emission targets and policy tools. Results suggest various useful policy implications for an environmentally and economically sustainable development of the country and provide long-term prospects for eﬀective and applicable energy policy solutions to foster investment into new technologies.
Keywords: Carbon -- Environmental aspects.; Climate change -- Turkey.